Any better?: A follow-up content analysis of adolescent sexual and reproductive health inclusion in Global Financing Facility country planning documents - Walmisley, Ulla; Kinney, Mary V.; Kiendrébéogo, Joël; Kafando, Yamba; George, Asha S. (Global health action, 2024)
The Global Financing Facility (GFF) supports national reproductive, maternal, newborn, child, adolescent health, and nutrition needs. Previous analysis examined how adolescent sexual and reproductive health was represented in GFF national planning documents for 11 GFF partner countries. This paper furthers that analysis for 16 GFF partner countries as part of a Special Series. Content analysis was conducted on publicly available GFF planning documents for Afghanistan, Burkina Faso, Cambodia, CAR, Côte d’Ivoire, Guinea, Haiti, Indonesia, Madagascar, Malawi, Mali, Rwanda, Senegal, Sierra Leone, Tajikistan, Vietnam. Analysis considered adolescent health content (mindset), indicators (measure) and funding (money) relative to adolescent sexual and reproductive health needs, using a tracer indicator. Countries with higher rates of adolescent pregnancy had more content relating to adolescent reproductive health, with exceptions in fragile contexts. Investment cases had more adolescent content than project appraisal documents. Content gradually weakened from mindset to measures to money. Related conditions, such as fistula, abortion, and mental health, were insufficiently addressed. Documents from Burkina Faso and Malawi demonstrated it is possible to include adolescent programming even within a context of shifting or selective priorities. Tracing prioritisation and translation of commitments into plans provides a foundation for discussing global funding for adolescents. We highlight positive aspects of programming and areas for strengthening and suggest broadening the perspective of adolescent health beyond the reproductive health to encompass issues, such as mental health. This paper forms part of a growing body of accountability literature, supporting advocacy work for adolescent programming and funding. Main findings: Adolescent health content is inconsistently included in the Global Financing Facility country documents, and despite strong or positive examples, the content is stronger in investment cases than project appraisal documents, and diminishes when comparing content, indicators and financing.Added knowledge: Although adolescent health content is generally strongest in countries with the highest proportion of births before age 18, there are exceptions in fragile contexts and gaps in addressing important issues related to adolescent health.Global health impact for policy and action: Adolescent health programming supported by the Global Financing Facility should build on examples of strong country plans, be more consistent in addressing adolescent health, and be accompanied by public transparency to facilitate accountability work such as this. Main findings: Adolescent health content is inconsistently included in the Global Financing Facility country documents, and despite strong or positive examples, the content is stronger in investment cases than project appraisal documents, and diminishes when comparing content, indicators and financing. Added knowledge: Although adolescent health content is generally strongest in countries with the highest proportion of births before age 18, there are exceptions in fragile contexts and gaps in addressing important issues related to adolescent health. Global health impact for policy and action: Adolescent health programming supported by the Global Financing Facility should build on examples of strong country plans, be more consistent in addressing adolescent health, and be accompanied by public transparency to facilitate accountability work such as this.